INTEGRATION OF THE THREE CENTERS OF EDUCATION AND RELIGIOUS MODERATION: A STRATEGY FOR STUDENT CHARACTER CONSTRUCTION IN INDONESIA IN THE ERA OF DISRUPTION - Moh. Subthi Buchori, Iffatul Lailiyah (PRODI PAI FIK UNIRA MALANG, 2026)
Moral degradation and intolerance among students due to globalization remain serious challenges. The implementation of character education within the 2013 Curriculum and the Merdeka Curriculum is hindered by theoretical approaches and weak collaboration among families, schools, and communities. This qualitative literature study formulates an integrative model combining Ki Hajar Dewantara's Three Centers of Education and Religious Moderation as a holistic character construction strategy. Data were thematically analyzed from journal articles, books, and policy documents using source triangulation. This research yields three main findings. First, the synergy of the Three Centers of Education requires active roles from families, teachers, and communities. Second, Religious Moderation is rooted in Islamic moderation (wasathiyah) and is uniquely integrated with local wisdom. Third, the effectiveness of this synergy is empirically confirmed, with an increase in students' moderate attitudes by up to 45%. This model aligns with Bronfenbrenner's Ecological Systems Theory and is characterized by a religio-cultural approach, structural involvement of community organizations, and utilization of local wisdom. Consequently, these findings contribute to presenting an ecological model that integrates the Three Centers of Education and Religious Moderation, along with strategic policy recommendations. This study underscores the need for a paradigm shift towards an ecosystem approach based on the collective commitment of all stakeholders.